The Role of Spirituality and Religiosity in Persons Living With Sickle Cell Disease: A Review of the Literature. (December 2016) - Clayton-Jones, Dora; Haglund, Kristin
Purpose: Sickle cell disease (SCD) is a serious debilitating chronic illness, affecting approximately 90, 000 Americans and millions globally. Spirituality and religiosity (S/R) may ease the burden faced by persons living with SCD. The purpose of this study was to examine the role of S/R in adolescents and adults living with SCD in the research literature.Method: The electronic databases Cumulative Index to Nursing and Allied Health Literature, Health Source Nursing/Academic, ProQuest Health Module, PsycINFO, Medline, PubMed, and the American Theological Library Association were searched from January 1995 to December 2014.Findings: Of the 89 studies retrieved, 11 articles between 2001 and 2013 met the inclusion criteria and were reviewed. Four themes emerged. The themes included (a) S/R as sources of coping, (b) S/R enhance pain management, (c) S/R influence health care utilization, and (d) S/R improve quality of life.Discussion: Use of S/R may be significant in coping with SCD, managing pain, affecting hospitalizations, and affecting quality of life. This review can direct researchers exploring S/R in adolescents and adults living with SCD.